New and interesting species of Emericella from Brazilian soil - Horie, Yoshikazu; Miyaji, Makoto; Nishimura, Kazuko; Franco, Marcello F. [UNESP]; Coelho, Kunie Iabuki R. [UNESP] (The Mycological Society of Japan, 1996)
Among the ascomycete isolates from soil and armadillo dung collected in Sao Paulo State, Brazil, a new species of Emericella, E. montenegroi and a new variety of E. rugulosa, E. rugulosa var. lazulina are described and illustrated. Emericella montenegroi differs from the other known species of the genus in having ascospores with an incompletely reticulate or ribbed ornamentation on the convex walls. Emericella rugulosa var. lazulina differs from the type variety in having blue to violet color of ascospores. Isolations of E. corrugata and E. foveolata are also reported as a South American record. A synoptic key to all accepted species of the genus is provided.
Keywords: Aspergillus montenegroi; Brazil; Emereicella corrugata; Emericella foveolata; Emericella montenegroi; Emericella rugulosa var. lazulina; soil fungi